Inclusão educacional da criança com autismo: estudo das tecnologias assistivas para ambientes digitais de aprendizagem - Santos, Lucirino Fernandes (2019)
The right to education of people with Autism Spectrum Disorder (ASD) reflects movements against socioeconomic and cultural injustices that, historically, affects people with deficiency, a scenery that it was sought to be changed from the paradigm of human rights, being the Specialized Educational Assistance (SEA) one of the mechanisms created to guarantee opportunity equalities, in the face of highly personal educational necessities that find in technology new possibilities. Based on that it is presented as research problem: - in what extent assistive technologies enabled by internet access contribute to the learning process of autistic child in Early Childhood Education and how public policies of human rights are being made effective to include these people inside of school environment? As a social justification, the research has the intention to identify failures and improvements in the public policy for social inclusion, creating reflexes in the exercise of citizenship and effectiveness of human rights of the autistic person, while it reveals the importance of promoting one education in/for human rights. Yet, it seeks to bring a reflection about the performance of inclusive educational teacher, with repercussions in the current Special Education policy, promoting the respect to diversity and the fight to the normalization of the “different”. Equally, it is evident the legal relevance once Brazilian State has assumed international, constitutional and infra constitutional commitments, producing knowledge about the social efficiency of regulatory declarations. As a general objective, it is analyzed if/how public policies designed to the insertion of assistive technologies in the school promote inclusion and if there is reverberation in the learning process of autistic child on the light of inclusive education paradigm. It stands out as theoretical contribution the Redistribution and Recognition Theory, the Socio Historical Theory and the Symbolic Constitutionalization Theory. Thus, it is aimed to contribute to the debate on technology regulation on the light of human rights encompassing the right to education of disabled person. Regarding to method, it was chosen an exploratory research, with mixed approach (quantitative and qualitative). Yet, in relation to the outline, a bibliographical, documentary and empirical research was carried out, with field study and observational method conjugated with data collection by the application of a questionnaire, being subject six inclusive education teachers who work in classes of multifunctional resources. It was adopted qualitative analysis with the corresponding data interpretation, with actions developed in three steps: reduction, exhibition and conclusion/verification. As a conclusion it was shown that assistive technologies which conform digital learning environments are an additional instrument to the autistic teaching-learning process, as well as there are local Public Authority actions to the implementation of SEA with the use of these tools, although, there is still a need to mitigate the inclusive deep gap in the face of problems in the social normative efficiency that aims to produce meaningful learning in the autistic development process.